Therapeutic potential of 7-oxo-DHEA as an adjunctive host-directed therapy for pulmonary tuberculosis - Vecchione, María Belén (2024)
Anti-tuberculous therapy successfully eradicates the infection, but it is long-lasting and impose the use of multiple drugs. Therefore, it is required to develop additional immunotherapy approaches to protect and manage human tuberculosis. In this study, we examined the properties of 7-oxo- dehydroepiandrosterone (7-oxo-DHEA), a DHEA-derivative hormone, through both in vitro and in vivo settings for M. tuberculosis (Mtb) infection. Firstly, we observed that 7-oxo-DHEA exhibited a bacteriostatic effect over Mtb growth. Furthermore, in an in vitro model of infection, 7-oxo-DHEA improved the killing of Mtb by human and murine macrophages and reduced the levels of anti-inflammatory cytokines secretion. Remarkably, 7-oxo-DHEA treatment moderated Mtb growth and lung injury during the progressive phase of TB disease in mice. Our findings demonstrate that this compound enhances immune responses, resulting in a more favorable profile for mycobacteria control. Further investigations are required to explore the potential use of 7-oxo-DHEA as a novel adjunctive host-directed treatment in the context of pulmonary tuberculosis disease, constraining Mtb infection and preventing severe lung injury.